A Ru(II)‐Based Nanoassembly Exhibiting Theranostic PACT Activity in NIR Region. (15th April 2020) - Wang, Youchao; Tian, Na; Sun, Weize; Rena, Boerhan; Guo, Xusheng; Feng, Yang; Li, Chao; Wang, Xuesong; Zhou, Qianxiong
Abstract: Photoactivated chemotherapy (PACT) has appealing merits over traditional chemotherapy as well as photodynamic therapy (PDT) by virtue of its spatial and temporal control on drug activity and oxygen‐independent mechanisms of action. However, the short photoactivation wavelengths, e.g., visible light–activated Ru(II)‐based PACT agents, limit the clinical application severely. In this work, a facile construction of supramolecular nanoparticles from a poly(ethylene glycol) (PEG)‐modified [Ru(dip)2 (py‐SO3 )] + (abbreviated as Ru‐PEG, dip = 4, 7‐diphenyl‐1, 10‐phenanthroline, py‐SO3 = pyridine‐2‐sulfonate) and 1, 3‐phenylenebis(pyren‐1‐ylmethanone) (BP) is shown. While Ru‐PEG may undergo photoinduced ligand dissociation and release anticancer species of [Ru(dip)2 (H2 O)2 ] 2+, BP has extremely large two‐photon absorption cross sections (δ2 ) in the NIR region and intense fluorescence over the wavelengths where Ru‐PEG has strong absorption. Thus, two‐photon excitation of BP followed by an efficient Förster resonance energy transfer (FRET) from BP to Ru‐PEG may lead to a potent inactivation against cisplatin‐resistant cancer cells and 3D multicellular tumor spheroids (MCTSs). The residue fluorescence of BP also allows the cellular uptake of the particles to be visualized. This work provides a universal and convenient strategy to realize theranostic PACT in the ideal phototherapeutic window of 650–900 nm. Abstract : A facile construction of supramolecular nanoparticles from poly(ethylene glycol) (PEG)‐modified [Ru(dip)2 (py‐SO3 )] + and 1, 3‐phenylenebis(pyren‐1‐ylmethanone (BP) with large two‐photon absorption cross sections and intense fluorescence is studied. The resultant theranostic Ru(II)‐PEG‐BP assembly exhibits efficient near‐infrared (NIR) excited photoactivated chemotherapy (PACT) activity toward cisplatin resistant cancer cells in 2D monolayers and 3D multicellular tumor spheroids (MCTSs).